All That Glitters Is Not Plumbate: Diffusion and Imitation of Plumbate Pottery during the Early Postclassic Period (AD 900–1200) at the Malpaís of Zacapu, Michoacán, Mexico. Issue 2 (June 2019) - Jadot, Elsa; Pereira, Grégory; Neff, Hector; Glascock, Michael D.
Abstract : In Mesoamerica, the Early Postclassic (AD 900–1200) is characterized by the long-distance circulation of pottery with a very hard and shiny coating with a metallic aspect, known as Plumbate ware. Plumbate is linked stylistically to the Toltec culture but was produced in workshops in Soconusco (Chiapas). The discovery of a similar collection of sherds during recent work at the site of El Palacio (Zacapu, Michoacán) shows that Plumbate ware also reached this region of Western Mexico. We carried out instrumental neutron activation analyses (INAA) on 11 of the Zacapu fragments and compared the results to the data from ceramic pastes from the region of Soconusco and Pátzcuaro Basin (Michoacán). Ten sherds were produced in Michoacán and are thus a local imitation, whereas the last fragment corresponds to a Tohil-type Plumbate paste and was transported over a long distance. This raises questions of the modalities for the circulation of this pot and the conditions allowing for production of an imitation (transfer of technical know-how?), which we suggest is linked to the Toltec culture in the center of Mexico. Abstract : En México, durante el Posclásico temprano (900–1200 dC), se destaca la circulación a larga distancia de vasijas caracterizadas por un engobe de aspecto metálico muy duro y particularmente brilloso: la cerámica Plomiza. Se ha podido constatar la presencia en el centro-oeste de México de tiestos del auténtico tipo Plomizo Tohil, producción típica de la región maya de Soconusco (Chiapas), como así también la existencia de una imitación michoacana, a 1600 km de Chiapas. Durante las excavaciones arqueológicas en el sitio urbano El Palacio (Cuenca de Zacapu, Michoacán, México) se hallaron varios tiestos de aspecto similar a la cerámica Plomiza. Para comprobar la hipótesis de una imitación local o de una importación, se realizaron análisis por activación neutrónica (INAA) en 11 fragmentos. Los datos fueron comparados con los de las pastas cerámicas de la región de Soconusco y de la Cuenca de Pátzcuaro (Michoacán). Los resultados muestran que 10 tiestos fueron realizados en Michoacán y, en consecuencia, son una imitación local, mientras que un tiesto corresponde a la pasta del tipo Plomizo Tohil lo cual implica su circulación a larga distancia. Esto lleva a plantear cuestiones sobre las modalidades de circulación de esta cerámica y las condiciones que permitieron su imitación (¿transferencias de habilidades técnicas?), que sugerimos vincular con la cultura tolteca del centro de México.